2020
DOI: 10.32491/jii.v20i3.532
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight relationship and condition factor of an endemic Lagusia micracanthus Bleeker, 1860 in Rivers of the Maros Watershed

Abstract: Lagusia micracanthus is one of endemic freshwater fish in Sulawesi. It also has been locally consumed. The purpose of this research was to analyze length-weight relationship and condition factors of L. micracanthus in rivers of the Maros Watershed, South Sulawesi Province . The study was conducted in three rivers, namely Pattunuang River, Bantimurung River and Pucak River. The sampling was conducted monthly from May 2018 to April 2019. Fish samples were collected by an electric shocker (12 V and 9 A). A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
0
7
0
7
Order By: Relevance
“…However, in this study, we only found endemic fish that belong to two families, namely Zenachopteridae and Adrinichthyidae. In The only fish from the Terapontidae family that lives in freshwaters with distribution is limited to certain rivers in South Sulawesi (Nur et al 2020a). This finding suggests that phylogenetic trees can describe the relationship between clades and taxonomic groups (Alotaibi et al 2020).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, in this study, we only found endemic fish that belong to two families, namely Zenachopteridae and Adrinichthyidae. In The only fish from the Terapontidae family that lives in freshwaters with distribution is limited to certain rivers in South Sulawesi (Nur et al 2020a). This finding suggests that phylogenetic trees can describe the relationship between clades and taxonomic groups (Alotaibi et al 2020).…”
Section: Discussionmentioning
confidence: 94%
“…Several ichthyofauna studies that have been done were on M. ladigesi, related to its morphology such as taxonomic status (Hadiaty 2007); sexual dimorphism, colour patterns, habitat and distribution (Hadiaty 2017); reproductive biology (Omar et al 2014;Kariyanti et al 2019;Nasyrah et al 2020); eco-biology (Nasyrah et al 2019); genetics (Jayadi et al 2015) and the length-weight relationship (Omar et al 2020). More research was also done on L. micracanthus on the fish description and historical tracing (Hadiaty 2012;Vari and Hadiaty 2012), reproductive biology (Andy Omar et al 2015;Nur et al 2016), morphometrics (Nur et al 2020a) and length-weight relationship (Nur et al 2020b). As for O. celebensis, the research covered its gonad development (Hamaguchi 1983) and reproductive biology (Hasanah et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Omar et al, (2020) explained that the condition factor of M. ladigesi in the Bantimurung River (male 1.0107 and female 1.0192) and the Pattunuang River (male 0.9850 and female 1.0044). The relative condition factors of Lagusia micracanthus was fluctuated from 0.86 to 1.43 in Pattunuang River, 0.65 to 1.45 in Bantimurung River, and 0.55 to 1.26 in Pucak River (Nur et al, 2020) According to Effendie (2002) that fish whose condition factor is 0-1, indicates that the fish were classified as flat or not fat fish. Table 5 shows that there are differences in the condition factors of male and female O. profundicola, allegedly due to the influence of the weight of the food contained in the digestive tract as well as the size, age of the fish and the environmental conditions in which the fish are located.…”
Section: Condition Factormentioning
confidence: 99%
“…Ikan pirik (Lagusia micracanthus) merupakan ikan air tawar endemik Sulawesi (Vari & Hadiaty, 2012;Nur et al, 2019;Nur et al, 2020a). Keunikan spesies ini adalah satu-satunya spesies ikan endemik Sulawesi yang berasal dari Genus Lagusia dan Family Terapontidae (monotypic genus) (Nur et al, 2020a).…”
unclassified
“…Ikan pirik (Lagusia micracanthus) merupakan ikan air tawar endemik Sulawesi (Vari & Hadiaty, 2012;Nur et al, 2019;Nur et al, 2020a). Keunikan spesies ini adalah satu-satunya spesies ikan endemik Sulawesi yang berasal dari Genus Lagusia dan Family Terapontidae (monotypic genus) (Nur et al, 2020a). Keunikan lainnya adalah persebarannya yang sangat terbatas yaitu hanya dapat ditemukan di satu Provinsi di Pulau Sulawesi yaitu Provinsi Sulawesi Selatan, itupun juga hanya dapat ditemukan pada sungai dengan karakteristik tertentu.…”
unclassified